X-RAY OPTICS : Imaging diffraction VLS spectrometer for a wavelength range λ > 120 Å. (30th January 2017) - Vishnyakov, E A; Kolesnikov, A O; Kuzin, A A; Negrov, D V; Ragozin, E N; Sasorov, P V; Shatokhin, A N
Abstract: A broadband stigmatic (imaging) soft X-ray (λ > 120 Å) spectrometer is experimentally realised. The optical configuration of the spectrometer comprises a plane grazing-incidence reflection grating with a spacing varying across its aperture according to a preassigned law [a so-called varied line-space (VLS) grating] and a broadband spherical normal-incidence mirror with an aperiodic Mo/Si multilayer structure. The average plate scale amounts to ∼5.5 Å mm -1 . The radiation is recorded with a matrix CCD detector (2048 × 1024 pixels of size 13 μm). The line spectra of the multiply charged ions LiIII and FV–FVII excited in laser-produced plasma are recorded with a spatial resolution of ∼26 μm and a spectral resolving power R ≈ 500 is experimentally demonstrated.